A descriptive analysis of design process in relation with the use of software applications of selected local garment retail companies - Geremillo, Sherry Liz C. (College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT Using the descriptive research method, the study sought to identify and describe the design outputs and software programs used by the design teams of selected local fashion retail companies. Applying the purposive sampling design, garment companies, which carry popular apparel and accessories for men and women, were the respondents. Specifically, two companies or three clothing brands agreed to take part in the research due to the confidentiality of data. Interviews with the design teams of Company A and Company B were conducted to obtain the data needed for the study. Also, earlier researches, studies and theories about CAD software, fashion design and retail business were used to guide the researcher through the study. In respect to the perspectives of the respondents, qualitative approach was used to analyze the primary data. The review of related literature was applied in describing and interpreting the data gathered. The results showed that many of the designers are familiar with the use of software programs. The specific design programs that they use are Adobe Photoshop CS3, CorelDRAW X4, Macromedia Freehand Illustrator 10 and Adobe?s Illustrator. The study also identified specific design outputs that the designers are able to produce using the design programs. These outputs include storyboards, flats and specs sheet. Storyboards are generated by using Adobe Photoshop CS3. Flats are created through the use of either CorelDRAW X4 or Macromedia Freehand Illustrator 10, as used specifically by Company A (Brand B), and Adobe Illustrator, as used specifically by Company B (Brand C). All of those said programs produce the specs sheet, because it 3 includes flat sketches and detailed specifications of garment parts such as color and fabric prints. Through the interviews, the study was able to identify the following benefits of each program: 1) Adobe Photoshop CS3 can refine the quality of photographs, scan other pictures and fabrics, and integrate them into the storyboard; 2) CorelDRAW X4 allows flat sketches to be oriented in grid line sections, which makes precise mapping of arrows to the artwork template; 3) Macromedia Freehand 10 can create and store multiple fashion illustrations of croquis and garment templates to easily recall previous designs and modify them, and 4) Adobe Illustrator can produce fashion illustrations and flat sketches with its versatile features as opposed to the other programs which can only be used with a particular design output. The study recommended the Design Teams of Brands A, B and C to undergo formal training of the use of software applications in their design process. In addition, the BSCT faculty can consider adding units on CAD courses to develop the students? competencies in using of a design program and prepare them for future jobs in the field of design and merchandising.